Pulmonary Embolism and Cardiovascular Care: Revolutionary Advances for the Decade Ahead - Thomas M. Loh; Alan B. Lumsden (Methodist DeBakey Cardiovascular Journal)
Introductory overview for Methodist DeBakey Cardiovascular Journal Issue 20.3 on Pulmonary Embolism, written by the issues’ guest editors.